Effect of Service Quality Lost and Found PT. Gapura Angkasa to Passenger Satisfaction at Bandung Husein Sastranegara International Airport - Tita Ismi Dwi Pitaloka; You She Melly Anne (CV. Rayyan Dwi Bharata, 2023)
As far as the author's observations while conducting pre-research at Husein Sastranegara International Airport in Bandung, the authors see that the lost and found service at Husein Sastranegara International Airport Bandung has deficiencies, namely in human resources (HR) there are only two officers per day. As the author observed, on November 9 2021, at the time of arrival of passengers, officers experienced difficulties dealing with passenger baggage problems, there were passengers who complained about problems with their missing luggage and there were also passengers who experienced luggage damage. The purpose of this study was to find out the services provided by Gapura Angkasa passasi officers in serving passengers to achieve passenger satisfaction. This research is expected to provide an overview for companies to determine the Effect of PT. Gapura Angkasa's Lost And Found Service Quality on Passenger Satisfaction at Husein Sastranegara International Airport Bandung. To further optimize and improve the services provided in order to prioritize passenger satisfaction. This study uses quantitative analysis methods to analyze the effect of the lost and found service quality of PT. Gapura Angkasa on passenger satisfaction at Husein Sastranegara Airport, Bandung. The population in this study were all passengers who used PT. Gapura Angkasa's lost and found service at Husein Sastranegara Airport, Bandung. The research sample used purposive sampling. The samples taken in this study were passengers using lost and found services based on age, occupation, and gender. The criteria for the respondents were passengers who used the lost and found service of PT. Gapura Angkasa Bandung Husein Sastranegara International Airport. The samples taken in this study were 50 respondents. Data collection techniques using questionnaires and documentation. The data analysis technique uses an instrument quality test which consists of a validity test, a reliability test. And test the hypothesis using simple linear regression analysis, T test and the coefficient of determination. Based on the data analysis carried out, it was concluded that there is a significant influence between the variables x (Influence of facilities) and Y (Passenger satisfaction). This can be done through SPSS passenger satisfaction has increased 1%, then the variable influence of facilities will also increase by 0.181. The coefficient is positive, so that it can be stated that there is a relationship between the independent variable (Service Effect) and the dependent variable (Passenger Satisfaction) and the T count 10.904 T table 1.353 with a significant value of 0.000 0.05, it can be concluded that the hypothesis (Ho) rejected, and (H1) accepted. the R relationship is 0.879 on the effect of lost and found service quality, which means that 87.9 has an effect on lost and found service quality at Husein Sastranegara Airport, Bandung.